The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.12693/aphyspola.128.b-239
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Anti-Inflammatory Activity of Flavonic Extract of Globularia alypum L.

Abstract: Globularia alypum L. of the family Globulariaceae is widely used in traditional medicine for its antiinflammatory activity. The aim of this study is to evaluate the anti-inflammatory activity of flavonic extract (butanol fraction) of globularia alypum against carrageenan induced paw-oedema in mice. The results have shown that the dose of 0.3 g/ml of butanol fraction present the most significant activity (33.01%) compared with reference product aspirine (39.76%) at dose of 2 mg/ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The analyses of the aqueous extract of GA leaves showed its abundance in secondary metabolites including flavonoids, iridoids, and phenylethanoid glucosoides. 10 GA extract showed many in vivo and in vitro biological activities such as anti-inflammatory activity against acetic acid-induced colitis in rats, 10 antioxidant effect against carrageenan-induced paw-edema in mice, 11 in vitro antimicrobial activity, 12 spermatogenesis activation in rats, 13 and vasodilatory effect in rat mesenteric arterial bed. 14 In the present study, we investigate the purgative/laxative effects of an aqueous extract of GA (GAAE) on gastrointestinal-physiological functions and against loperamide (LOP)-induced constipation coupled to oxidative stress in rats.…”
mentioning
confidence: 99%
“…The analyses of the aqueous extract of GA leaves showed its abundance in secondary metabolites including flavonoids, iridoids, and phenylethanoid glucosoides. 10 GA extract showed many in vivo and in vitro biological activities such as anti-inflammatory activity against acetic acid-induced colitis in rats, 10 antioxidant effect against carrageenan-induced paw-edema in mice, 11 in vitro antimicrobial activity, 12 spermatogenesis activation in rats, 13 and vasodilatory effect in rat mesenteric arterial bed. 14 In the present study, we investigate the purgative/laxative effects of an aqueous extract of GA (GAAE) on gastrointestinal-physiological functions and against loperamide (LOP)-induced constipation coupled to oxidative stress in rats.…”
mentioning
confidence: 99%
“…According to ethnobotanical surveys, G. alypum is one of the most important medicinal plants in Algieria, traditionally used as an antidiabetic, laxative, stomachic, and purgative agent, mainly due to the occurrence of such compounds as flavonoids, tannins and iridoids [ 24 , 25 , 26 ]. However, the occurrence of triterpenoids, particularly betulin as well as ursolic acid, can be of interest in the context of the reported anti-inflammatory [ 47 ] and antituberculosis [ 24 ] activities, exerted by methanol and petroleum ether extracts, which might contain these low-polar compounds. Moreover, it was demonstrated that the best activity against Mycobacterium tuberculosis was obtained for the petroleum ether extract; therefore, the potential synergism of triterpenoids with other bioactive constituents cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“… 64 Flavonoids, as phenolic compounds, have been shown to have anti-oxidant effects on many chronic diseases such as diabetes, cancer, Alzheimer's disease, and cardiovascular disease caused by oxidative stress. 65 The plant also contains copper, manganese, folate, and a high concentration of bioactive compounds, including saponins, coumarins, flavonoids, phytosterols, phytoestrogens, and alkaloids. Saponins exist in alfalfa have heart-protective effects due to their cholesterol-lowering activity.…”
Section: Discussionmentioning
confidence: 99%